Impact of disease location on fecal calprotectin levels in Crohn's disease. (July 2015) - Gecse, Krisztina B.; Brandse, Johannan F.; van Wilpe, Sandra; Löwenberg, Mark; Ponsioen, Cyriel; van den Brink, Gijs; D'Haens, Geert
Abstract: Objective. The correlation between the Simple Endoscopic Score for Crohn's Disease (SES-CD) and fecal calprotectin is well established in (ileo)colonic Crohn's disease (CD). However, for ileal CD, existing data are conflicting. The aim of this study is to evaluate the biomarker profile in CD patients with varying severity and location of mucosal ulceration. Materials and methods. An electronic patient database search identified CD patients in whom ileocolonoscopy, fecal calprotectin (CALPRO), serum C-reactive protein (CRP) and blood leukocyte counts (LEU) were measured within a 4-week interval without changes in medication. Ileocolonoscopies were scored for the presence of ulcers in each segment as defined by the SES-CD and the sum of segmental ulcer scores resulted in a partial SES-CD (pSES-CD). Results. Fourty-four patients were identified, of whom 9/44 had ileal CD, 20/44 colonic and 15/44 ileocolonic CD based on the Montreal classification. In the total study population CALPRO correlated best with pSES-CD (r = 0.76, p < 0.0001), followed by LEU (r = 0.54, p = 0.0004) and CRP (r = 0.45, p = 0.0026). Patients with ileal CD had significantly lower CALPRO level than those with (ileo)colonic disease even in the presence of large and/or very large ulcers (mean ± SEM: 297 ± 81 μg/g vs. 1523 ± 97 μg/g, p < 0.0001). LEU was also significantly lower in the presence of large and/or very large ulcers in ileal CD compared to those with (ileo)colonic disease (mean ± SEM: 6.7 ± 0.9 × 10 9 /l vs. 10.6 ± 0.8 × 10 9 /l, p = 0.02). A similar trend was identified regarding CRP levels. Conclusions. Even in the presence of large or very large ulcers, patients with ileal Crohn's may not have markedly elevated fecal calprotectin levels.